Does Parenthood Change Attitudes to Fathering? Evidence from Australia and Britain - Buchler, S; Perales, F; Baxter, Janeen (My University, 2017)
A wealth of research has established that the transition to parenthood can shift men’s and women’s attitudes to motherhood. We add to this knowledge base by examining how attitudes to fatherhood change across the transition to parenthood. This is important within a historical period in which definitions of what it means to be a good father are changing to emphasise hands-on involvement in childcare, yet there has been little institutional change to support this. Our empirical analyses rely on long-running, panel data from Britain and Australia, and fixed-effect panel regression models. We find that attitudes to fatherhood change significantly after the birth of a first child. For most of the measures considered, parenthood results in men’s attitudes to fatherhood becoming comparatively more egalitarian than women’s. While both Australian and British men become more enthusiastic towards being involved in the care and upbringing of their children after experiencing parenthood, Australian women become less likely to agree that fathers should do so. These findings provide a partial explanation for why couples engage in more traditional gender divisions of labour after parenthood. They suggest that men’s involvement in childcare is not only constrained at the institutional and employment levels, but also by their female partners becoming more reluctant to support an active fathering role. More broadly, our research adds to growing evidence demonstrating that first births are an important life-course marker, and parenthood has the capacity to shift how men and women perceive their familial roles and their broader roles in society.
Sex Roles
Keywords: Families -- Parents and Parenting; Beliefs and Values; Families and relationships; Families; Beliefs and Values; Parents and Parenting; Families and relationships